The genus Cangshanaltica (Coleoptera: Chrysomelidae: Alticinae): overview, new species, and notes on species complexes - Damaška, Albert František; Ruan, Yongying; Fikáček, Martin (Zootaxa, 2022)
Moss-inhabiting flea beetles form a diversified ecological group of beetles with a number of recently described new species. Here, we present an overview of known species of the moss-inhabiting flea beetle genus Cangshanaltica Konstantinov, Chamorro, Prathapan, Ge & Yang, 2013 which is distributed in Eastern and South-Eastern Asia. We describe three new species: Cangshanaltica guanxiensis sp. nov. from Guanxi, China, C. marginata sp. nov. from Yunnan, China, and C. javana sp. nov., from Java, Indonesia. Additionally, we redescribe Cangshanaltica castanea (Gruev, 1985) comb. nov., a species formerly placed in Ivalia. Based on our studies of the morphological characters, we assume that some of the currently recognized species may in fact represent species complexes. Our findings also extend the known distribution of Cangshanaltica to Indonesia. A key of all described Cangshanaltica species, and an annotated checklist are provided.